Birth and rapid subcellular adaptation of a hominoid-specific CDC14 protein. - Lia Rosso; Ana Claudia Marques; Manuela Weier; Nelle Lambert; Marie-Alexandra Lambot; Pierre Vanderhaeghen; Henrik Kaessmann (PLoS Biology, 2008)
Gene duplication was prevalent during hominoid evolution, yet little is known about the functional fate of new ape gene copies. We characterized the CDC14B cell cycle gene and the functional evolution of its hominoid-specific daughter gene, CDC14Bretro. We found that CDC14B encodes four different splice isoforms that show different subcellular localizations (nucleus or microtubule-associated) and functional properties. A microtubular CDC14B variant spawned CDC14Bretro through retroposition in the hominoid ancestor 18-25 million years ago (Mya). CDC14Bretro evolved brain-/testis-specific expression after the duplication event and experienced a short period of intense positive selection in the African ape ancestor 7-12 Mya. Using resurrected ancestral protein variants, we demonstrate that by virtue of amino acid substitutions in distinct protein regions during this time, the subcellular localization of CDC14Bretro progressively shifted from the association with microtubules (stabilizing them) to an association with the endoplasmic reticulum. CDC14Bretro evolution represents a paradigm example of rapid, selectively driven subcellular relocalization, thus revealing a novel mode for the emergence of new gene function.